Design and Implementation of the MTX Operating System - Wang, K. C. (Springer International Publishing : Imprint: Springer, 2015)
This course-tested textbook describes the design and implementation of operating systems, and applies it to the MTX operating system, a Unix-like system designed for Intel x86 based PCs. Written in an evolutional style, theoretical and practical aspects of operating systems are presented as the design and implementation of a complete operating system is demonstrated. Throughout the text, complete source code and working sample systems are used to exhibit the techniques discussed. The book contains many new materials on the design and use of parallel algorithms in SMP. Complete coverage on booting an operating system is included, as well as, extending the process model to implement threads support in the MTX kernel, an init program for system startup and a sh program for executing user commands. Intended for technically oriented operating systems courses that emphasize both theory and practice, the book is also suitable for self-study.